THE SYSTEMATIC REVIEW OF SCREENING MAMMOGRAPHYBEYOND BREAST CANCER - Yoga Nuswantoro, Yoga; Anggraini, Efa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: It is critical to assess the effects of coordinated mammography service screening separately from modifications to breast cancer therapy. This can be achieved by calculating the fatal breast cancer incidence, which is determined by the diagnostic date rather than the death date. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 109 articles, whereas the results of our search on SagePub brought up 98 articles. The results of the search conducted for the last year of 2013 yielded a total 45 articles for PubMed and 32 articles for SagePub. In the end, we compiled a total of  5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, mammography screening lowers the death rate from breast cancer, although the estimates are only marginally statistically significant, the effects are modest at younger ages, and the way cases were accumulated in trials affects the outcome. Screening for cancers at higher stages also lowers the risk of cancer in those 50 and older.